Synthesis of magnetic polymeric ionic liquid nanocomposites by the Radziszewski reaction - Castro Grijalba, Alexander (2017)
In the present article a new approach for the synthesis of magnetic polymeric ionic liquid nanocomposites based on the Radziszewski reaction is presented. The Radziszewski reaction is a simple and successful procedure to obtain imidazolium-containing polymers under mild conditions and consists of the reaction between diamine compounds, glyoxal and formaldehyde in an acidic media. If magnetic nanoparticles coated with amino groups are introduced, they can participate as polyamines in the synthesis thus providing a final nanocomposite where polymeric ionic liquids and nanoparticles are combined. The resulting nanocomposite has been characterized using several instrumental techniques aimed at elucidating its chemical composition (infrared spectroscopy and elemental analysis), properties (zeta potential) and morphology (microscopy, X-ray diffraction and dynamic light scattering). Finally, its sorptive ability towards three non-steroidal anti-inflammatory drugs (NSAIDs) such as salicylic acid, ketoprofen and naproxen was evaluated considering the main variables involved in the process. According to the results, the polymeric ionic liquid nanocomposite is a promising sorptive material for analytical purposes.